2018
DOI: 10.1021/acs.nanolett.8b02161
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Single-Cycle Near Field in a Tunnel Junction with Carrier-Envelope Phase-Controlled Terahertz Electric Fields

Abstract: Light-field-driven processes occurring under conditions far beyond the diffraction limit of the light can be manipulated by harnessing spatiotemporally tunable near fields. A tailor-made carrier envelope phase in a tunnel junction formed between nanogap electrodes allows precisely controlled manipulation of these processes. In particular, the characterization and active control of near fields in a tunnel junction are essential for advancing elaborate manipulation of light-field-driven processes at the atomic-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 49 publications
7
62
0
Order By: Relevance
“…The control strategy reported here and based on the dc bias applied between the antenna arms operates simultaneously with earlier studied coherent control using the CEP of the incident pulse [23,35,36]. Our study thus establishes a conceptual basis to extend the application of static or THz fields beyond the control of electron (photo)emission from metallic tips [14][15][16][17][18][19] and electron tunneling [37][38][39]. Along with dielectric, semiconductor [40][41][42][43], graphene-based [20,44], and tunneling [36] structures, the theoretical and experimental realization demonstrated here, analog to an ultrafast rectifying vacuum diode (see also [31]), paves the way towards petahertz electronics [45].…”
mentioning
confidence: 56%
“…The control strategy reported here and based on the dc bias applied between the antenna arms operates simultaneously with earlier studied coherent control using the CEP of the incident pulse [23,35,36]. Our study thus establishes a conceptual basis to extend the application of static or THz fields beyond the control of electron (photo)emission from metallic tips [14][15][16][17][18][19] and electron tunneling [37][38][39]. Along with dielectric, semiconductor [40][41][42][43], graphene-based [20,44], and tunneling [36] structures, the theoretical and experimental realization demonstrated here, analog to an ultrafast rectifying vacuum diode (see also [31]), paves the way towards petahertz electronics [45].…”
mentioning
confidence: 56%
“…In the present work, using THz-STM coupled with a CEP shifter for broadband THz pulses [9], we demonstrate that desirable phase-controlled THz near-fields can be produced in a tunnel junction [10]. Measurements of the phase-resolved sub-cycle electron tunneling dynamics revealed a large CEP shift between the THz far-and near-field waveforms.…”
Section: Introductionmentioning
confidence: 65%
“…2(b), the bidirectional sub-picosecond electron burst was generated by adjusting the CEP-controlled pulse to yield a sinusoidal near-field in the junction. Furthermore, we found that the timing and direction of ultrafast electron burst can be manipulated over the femtosecond timescale by actively control the THz near-field with precisely adjusting the CEP of CEP-controlled pulse [10].…”
Section: Resultsmentioning
confidence: 99%
“…Terahertz scanning tunneling microscope (STM) (THz-STM) is capable of imaging surfaces with atomic spatial resolution and the subpicosecond time resolution (<0.5 ps), much faster than conventional STM system [15,17,19,20,76,77]. The basic principle of THz-STM is quantum tunneling through the gap between the tip and sample resulting from a transient voltage induced by terahertz pulses.…”
Section: Terahertz Scanning Tunneling Microscopementioning
confidence: 99%